2020
DOI: 10.1002/lrh2.10218
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Health System Competency Appraisal Inventory (LHS‐CAI): A novel tool for assessing LHS‐focused education needs

Abstract: There is increasing interest in health care organizations functioning as learning health systems (LHSs) to improve the quality and efficiency of health care delivery while generating new knowledge. Individuals must be trained in associated concepts and competencies and subsequently positioned (or embedded) within the delivery system for maximum effect as they perform their scholarship. Potential researchers within LHSs come from many different training backgrounds; therefore, each LHS scholar requires a goal-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“… 7 Greenberg-Worisek et al subsequently identified the domains from this work as competencies required of healthcare providers working in LHS. 15 However, this author did not consider the alignment between the competencies identified by Forrest et al and the skills and knowledge required by practitioners beyond identification of the domains. 7 Further research should explore which of the specific competencies as identified by Forrest et al should be developed for practitioners working in LHS and should also focus on the competencies of patients in the LHS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 7 Greenberg-Worisek et al subsequently identified the domains from this work as competencies required of healthcare providers working in LHS. 15 However, this author did not consider the alignment between the competencies identified by Forrest et al and the skills and knowledge required by practitioners beyond identification of the domains. 7 Further research should explore which of the specific competencies as identified by Forrest et al should be developed for practitioners working in LHS and should also focus on the competencies of patients in the LHS.…”
Section: Discussionmentioning
confidence: 97%
“…Ten articles addressed practitionerrelated competencies, with early work done in the field of nursing. [14][15][16][17][18][19][20][21][22][23] Early work emphasised skills in evidence-based practice. 14 21 These skills included the ability to use guidelines and quality improvement programmes for evidence-based practice, the ability to use electronic health record (EHR) data to assess quality and provide quality care and the ability to use practice guidelines and clinical decision support (CDS) for evidence-based practice.…”
Section: Thematic Analysismentioning
confidence: 99%
“…2 , 3 The Agency for Healthcare Research and Quality (AHRQ) and the Patient‐Centered Outcomes Research Institute (PCORI) have seen the development of the LHS as a key strategy to help healthcare organizations make transformational changes to improve healthcare quality and value, and have invested in efforts to promote the development, synthesis, and rapid movement of new evidence into practice. 4 A brief but representative list of publications 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 from our institutions is included in the references. This selection contributes, if fractionally, to a rapidly growing body of impactful literature on the LHS.…”
Section: Introductionmentioning
confidence: 99%
“…Our survey is distinctly different from prior work that developed an appraisal inventory to help direct LHS scholar's individual development plans and which utilized the core competency statements verbatim 12 . We revised some language in the original core competencies and wrote separate survey items for those core competencies that contained multiple components.…”
Section: Discussionmentioning
confidence: 99%
“…The ease of understanding the wording of the item (ie, the meaning of the item is clear and is free of overly vague language or unnecessary jargon) Our survey is distinctly different from prior work that developed an appraisal inventory to help direct LHS scholar's individual development plans and which utilized the core competency statements verbatim. 12 We revised some language in the original core competencies and wrote separate survey items for those core competencies that contained multiple components. Feedback from a multidisciplinary expert panel in rehabilitation was used to enhance clarity of language, and relevance for the rehabilitation research community.…”
Section: Claritymentioning
confidence: 99%